2021
DOI: 10.1091/mbc.e21-03-0146-t
|View full text |Cite
|
Sign up to set email alerts
|

L-bodies are RNA–protein condensates driving RNA localization in Xenopus oocytes

Abstract: RNP granules are membrane-less compartments within cells, formed by phase separation, that function as regulatory hubs for diverse biological processes. However, the mechanisms by which RNAs and proteins interact to promote RNP granule structure and function in vivo remain unclear. In Xenopus laevis oocytes, maternal mRNAs are localized as large RNPs to the vegetal hemisphere of the developing oocyte, where local translation is critical for proper embryonic patterning. Here, we demonstrate that RNPs containing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 92 publications
(229 reference statements)
1
44
0
2
Order By: Relevance
“…Nevertheless, we argue that the selective inclusion of large-size polymeric components such as RNA and DNA into one of the phases is responsible for causing a significant dynamic asymmetry between the two phases and inducing VPS. We demonstrate that this scenario can well explain recent experimental findings in mesh-like or network-like structure formation in TIS granules network 13,14 , RNP (ribonucleoprotein) granules 15 , localisation bodies 16 , FXR1 condensates 17 , NLRP6 18 and centrosome assemblies 21,23,38 .…”
supporting
confidence: 81%
See 3 more Smart Citations
“…Nevertheless, we argue that the selective inclusion of large-size polymeric components such as RNA and DNA into one of the phases is responsible for causing a significant dynamic asymmetry between the two phases and inducing VPS. We demonstrate that this scenario can well explain recent experimental findings in mesh-like or network-like structure formation in TIS granules network 13,14 , RNP (ribonucleoprotein) granules 15 , localisation bodies 16 , FXR1 condensates 17 , NLRP6 18 and centrosome assemblies 21,23,38 .…”
supporting
confidence: 81%
“…These aggregates lose their coalescence ability and tend to form network-like structures. Such networklike or irregular-droplet morphology has also been discovered in TIS (TPA (12-0-tetradecanoyl-phorbol-13-acetate)-inducible sequence protein) granules 13,14 , RNP (ribonucleoprotein) granules 15 , localisation bodies 16 , FXR1 (fragile X mental retardation syndrome-related protein 1) condensates 17 and NLRP6 (nucleotide-binding oligomerization domain-like (NOD-like) receptor family pyrin domain containing 6) 18 (see also recent reviews 6,19 ). This type of morphology provides a large interface area with a bicontinuous nature, crucial for biological reactions and transport.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…In vitro , low concentrations of RNA often promote liquid-liquid phase separation (LLPS) of proteins ( Burke et al., 2015 ; Lin et al., 2015 ; Molliex et al., 2015 ; Patel et al., 2015 ), whereas high concentrations can inhibit LLPS ( Banerjee et al., 2017 ; Maharana et al., 2018 ). Conversely, many RNAs are capable of protein-free self-assembly ( Jain and Vale, 2017 ; Langdon et al., 2018 ; Neil et al., 2021 ; Van Treeck et al., 2018 ). In vivo , recent studies have shown that RNA may be acting to form a non-dynamic or structural component within a variety of biomolecular condensates ( Clemson et al., 2009 ; Neil et al., 2021 ; Niepielko et al., 2018 ; Trcek et al., 2020 ; Van Treeck et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%